Functional components and sensory evaluation of yacon (Polymnia soncifolia L.) chips at various drying conditions. - Duro, H. L.; Hurtada, W. A.; Rodriguez, F. M. (2003)
Yacon is a crop that has gained popularity for its nutritional and healing properties. This research was conducted to assess changes in the functional properties of yacon as affected by oven drying temperatures (60, 70 and 80 °C) and length of drying time (11, 13 and 15 hr). Sensory evaluation was also conducted to evaluate the acceptability of the processed yacon chips. Increasing the drying temperature increased the antioxidative activity and total phenol count and decreased the saponins and flavonoid content and reducing power of the yacon chips. Alkaloid content was high and generally unaffected by the drying treatments. On the other hand, tannin content increased only with an increase in drying time within a given temperature. Sensory evaluation showed that the flavour, color, aroma, texture and general acceptability were unaffected by the temperature used and the length of time of processing.
Keywords: Yacon